Comparative performance of linseed (Linum usitatissimum) varieties under mango (Mangifera indica) based agroforestry in sub-tropical region of central India - Kavya K L; Dongre, Rahul; Malaviya, Poornima (Indian Journal of Agroforestry, 2023)
The present study was aimed to investigate the productivity of linseed varieties under mango based agroforestry practice and sole cropping conditions. Additionally, economic assessment was done to understand the economic viability of the land use practices. The experiment was conducted at Forestry Research Farm, Department of Forestry, Jawaharlal Nehru Krishi Vishwa Vidyalaya, Jabalpur during Rabi season of 2020-2021. The experiment was laid out in randomized block design and had eight treatments with five replications. It included four varieties of linseed crop (JLS-9, JLS-73, JLS-27, JLS-66) under mango based agroforestry as, Mango + JLS-9, Mango + JLS-73, Mango + JLS-27, Mango + JLS-66 and under sole cropping condition as sole JLS-9, sole JLS-73, sole JLS-27, sole JLS-66. Significantly maximum (79.9 cm) plant height at harvest found for JLS-27. While it was recorded minimum (67.6 cm) for JLS-73. Variety JLS-27 and JLS-9 found significantly maximum (9.2, 9.0 respectively) for seeds per capsule. While JLS-66 and JLS-73 recorded minimum (7.5, 7.6 respectively). Significantly highest seed yield (712.6 Kg ha-1) and harvest index (33.3 %) was recorded for JLS-66. While minimum seed yield (637.2 Kg ha-1) and harvest index (29.9 %) was recoded for JLS-73. The highest gross and net monetary return was obtained for variety JLS-66. B: C ratio was maximum for JLS-66 (2.44) under sole cropping condition, followed by JLS-9 and JLS-27. While it was minimum for JLS-7 (1.60) under mango. Based on the experimental findings, the productivity of linseed did not differ significantly under different land use practices. B: C ratio of JLS-66 (sole) variety was maximum as compared to all other linseed varieties. It was followed by JLS-9 and JLS-27. While minimum was found for JLS-73. Key words: Agri-horticulture system, Mango, sole cropping, Jawahar Linseed Varieties (JLS), B:C ratio